CCAFS Household Baseline Study, Latin America & South East Asia (2014-2015) - Garlick, Cathy; Förch, Wiebke (2015)
This dataset contains files produced for and generated from the CCAFS Household Baseline Study carried out in sites in Latin America (Trifinio in Honduras/Guatemala, and Cauca in Colombia) and in South-East Asia (a site in each of Cambodia, Laos and Vietnam) in the latter months of 2014 and the early months of 2015. There are six sites in all (two sites from Trifinio). Before downloading any of the files, particularly the data files, please download and read the CCAFS ReadMe file which is prefixed by the code 0000. To gain access to the GPS coordinates from the restricted files please download and complete the Non-disclosure agreement from the file "0002 Non-Disclosure Agreement 2013-01-20.pdf" and send this to Wiebke Foerch at w.foerch@cgiar.org The study was based on earlier baseline studies carried out in sites in West and East Africa and in South Asia. Data and other files from these earlier studies are available in a separate dataset in this Dataverse archive. (CCAFS Household Baseline Survey 2010-2012). If you are intending to use data from both studies together we suggest you read the file "0001 Questionnaire Differences & Recoding Details 2015-10-29.pdf" which explains differences between the two studies.